1998
DOI: 10.1029/98gl02153
|View full text |Cite
|
Sign up to set email alerts
|

Local heating/cooling of the mesosphere due to gravity wave and tidal coupling

Abstract: Abstract. Numerical experiments in this study show that the tidal wind may have strong impacts on the stability of the gravity wave and therefore significantly affects the breaking of the gravity wave. This enhances the local dynamical cooling and turbulence heating, and produces descending heating/cooling structures, which are similar to recent lidar observations. The propagating phase of such structures is dependent on the descending phase of the tidal wave and the gravity wave breaking level. The maximum he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 11 publications
5
100
1
Order By: Relevance
“…Wind fluctuations, on the other hand, are bound to approach zero amplitude at the poles. Walterscheid (1981), Fritts and Vincent (1987), Liu and Hagan (1998) and Liu et al (2000) have proposed that gravity wave modulation by the tide may produce an enhanced artificial tide at levels above the modulation region. However, it is not clear that this could produce a tidal magnification of a factor of 2 or 3.…”
Section: Discussionmentioning
confidence: 99%
“…Wind fluctuations, on the other hand, are bound to approach zero amplitude at the poles. Walterscheid (1981), Fritts and Vincent (1987), Liu and Hagan (1998) and Liu et al (2000) have proposed that gravity wave modulation by the tide may produce an enhanced artificial tide at levels above the modulation region. However, it is not clear that this could produce a tidal magnification of a factor of 2 or 3.…”
Section: Discussionmentioning
confidence: 99%
“…Meriwether et al (1994), using Rayleigh lidar observations, also observed similar wave activity with downward phase propagation for winter events. Their numerical, two-dimensional model of gravity wavetidal coupling points strongly to the conclusion that breaking gravity waves may play a significant role by amplifying the temperature amplitude of the tidal structure and production of large MILs (Liu et al, 1998(Liu et al, , 1999(Liu et al, , 2000. Recently, Meriwether et al (2000) have given a thorough review of MILs and explained the possible causes for the occurrence of MILs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to observational studies, numerical models have been employed extensively to study tidal-GW interactions (Forbes et al, 1991;McLandress and Ward, 1994;Eckermann and Marks, 1996;Liu and Hagan, 1998;Mayr et al, 1998Mayr et al, , 2001Meyer, 1999;Norton and Thuburn, 1999;Liu et al, 2000;Akmaev, 2001;England et al, 2006;Ortland and Alexander, 2006;Liu et al, 2008;Senf and Achatz, 2011). Based on these observational and numerical studies, we know that tidal-GW interactions can, among others, (1) change the local wind and temperature, e.g., by forming temperatureinversion layers (Liu and Hagan, 1998;Meriwether et al, 1998;Sica et al, 2002;Sridharan et al, 2008); (2) cause short-term and seasonal variability of tidal structures (Mayr et al, 1998;Meyer, 1999); (3) modulate GWs' energy and momentum flux (Beldon and Mitchell, 2010); and (4) lead to GW instability and dissipation at the critical layers (Williams et al, 2006).…”
Section: Introductionmentioning
confidence: 99%